2020
DOI: 10.35848/1347-4065/ab6f2d
|View full text |Cite
|
Sign up to set email alerts
|

Drift compensation in dual start/stop data acquisition positron lifetime measurements

Abstract: When analyzing positron annihilation lifetime spectra with multiple components using an exponential function with a single component, there is a difference between the experimental data and the fitted spectrum. Compensating for this difference causes a shift in the starting time (T 0) in the fitted spectrum. Previously, we applied single-component analysis to the positron lifetime spectrum of a defect-containing metal and confirmed the effectiveness of the shift in T 0 (ΔT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Furthermore, we reported that the drift in the positron lifetime spectrum, caused by temporal instability of photomultiplier and high-voltage power supply can be corrected using dual start stop data acquisition. 19,20) On comparing the behaviors of the centre-of-gravity positron lifetime, the "mean" positron lifetime and ΔT 0 , we observed that the first two markedly change only in lowdefect-density regions, while the third showed a considerable change in the high defect densities but with complicated dependency on defect density. Based on this fact, obtaining information about the defects in a wide-density range from the positron lifetime data may be possible by combining multiple parameters with varying dependencies on the defect density.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, we reported that the drift in the positron lifetime spectrum, caused by temporal instability of photomultiplier and high-voltage power supply can be corrected using dual start stop data acquisition. 19,20) On comparing the behaviors of the centre-of-gravity positron lifetime, the "mean" positron lifetime and ΔT 0 , we observed that the first two markedly change only in lowdefect-density regions, while the third showed a considerable change in the high defect densities but with complicated dependency on defect density. Based on this fact, obtaining information about the defects in a wide-density range from the positron lifetime data may be possible by combining multiple parameters with varying dependencies on the defect density.…”
Section: Introductionmentioning
confidence: 88%
“…In this study, the positron annihilation lifetime measurement was performed using the commercial system, PSA TypeL-II [8][9][10][11] manufactured by TOYO SEIKO Co., Ltd. (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Precise determination of ΔT 0 is possible with the anti-coincidence positron lifetime measurement [8]. If the anti-coincidence lifetime measurement is combined with dual start/stop data acquisition [9], ΔT 0 can be determined even more precisely. As a result of the simulation, it was clarified that different positron lifetime spectra with large statistical errors can be distinguished in a wide region of trapping rates up to 10 11 s −1 by using the two-dimensional plot of ΔT 0 and τm [10].…”
Section: Introductionmentioning
confidence: 99%